2004
DOI: 10.1021/om034234d
|View full text |Cite
|
Sign up to set email alerts
|

α,ω-Diferrocenyl Cumulene Molecular Wires Studied by Density Functional Theory

Abstract: Density functional theory calculations for neutral and oxidized diferrocenyldiphenylcumulenes, [Fc(Ph)C n (Ph)Fc] with n ) 2, 4, 6, 8, were performed at the B3LYP/6-31G level without any restrictions in symmetry. Geometrically, of the four possible diasteromeric structures of the neutral cumulenes, no preferential conformation was revealed, and the calculated structures reproduce the experimental X-ray structural data quite well. The spin density of all mono-and dications is located on the iron atoms, but not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…In addition to ferrocene, results for the derivatives of other iron and chromium π ‐complexes (bis(benzene)chromium (η 6 ‐C 6 H 6 )Cr(η 6 ‐C 6 H 6 ), benzene chromium tricarbonyl (η 6 ‐C 6 H 6 )Cr(CO) 3 , and cyclobutadiene‐iron tricarbonyl (η 4 ‐C 4 H 4 )Fe(CO) 3 ) have been reported . It has been shown that the δ values and localization degree of 3 d AOs are stable and universal.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to ferrocene, results for the derivatives of other iron and chromium π ‐complexes (bis(benzene)chromium (η 6 ‐C 6 H 6 )Cr(η 6 ‐C 6 H 6 ), benzene chromium tricarbonyl (η 6 ‐C 6 H 6 )Cr(CO) 3 , and cyclobutadiene‐iron tricarbonyl (η 4 ‐C 4 H 4 )Fe(CO) 3 ) have been reported . It has been shown that the δ values and localization degree of 3 d AOs are stable and universal.…”
Section: Methodsmentioning
confidence: 99%
“…As the chain lengthens, some negative charge flows towards the midpoint. Thus, 77 % of the total charge on the chain in PtC 26 Pt is found at C1/C2. Charge alternation patterns also develop.…”
Section: Chain-length Effectsmentioning
confidence: 99%
“…Now the cumulative bond orders decrease from 2.664 to 2.600 (2.4 %), again with no change in the s population. Indeed, all CC bonds undergo bond-order reduction through the p manifold, although comparisons must be made over narrower ranges (e.g., from PtC 10 Pt to PtC 26 Pt for C5/C6 CC). In contrast, the C2/C3 CÀC single bond order shows a gradual increase from 0.967 to 0.973 (0.62 %).…”
Section: Chain-length Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar strategy was recently reported to yield good predictions of the properties of ferrocene-containing molecules. [38] Compound 3 can adopt several conformations. In particular, we considered the conformation at the carboxylic acid group, the conformation at the two ester groups, and the conformation at the ether group.…”
Section: Full Papermentioning
confidence: 99%